International relations a very short introduction - Reus-Smit, Christian (Very short introductions, 2020)
International relations affect everyone's lives: their security, economic well-being, rights and freedoms, and the environment they share. Recently we have seen the transformation from a world of empires to today's world of sovereign states, which are enmeshed in a complex array of international institutions, all exercising degrees of political authority. The new global organization of political authority has far-reaching consequences. This Very Short Introduction untangles this complex world, providing an accessible framework for understanding the contours of global political change. Christian Reus-Smit treats theory as an indispensable tool for grasping international relations, but demystifies theorizing, introducing it as an everyday human practice. He surveys a range of theories, from realism to feminism: reading them as contrasting perspectives on the global organization of political authority. Historically, such organization has been shaped by diverse social forces, four of which are discussed in detail: shifting patterns of warfare, changing economic conditions, struggles for rights, and the politics of culture. Reus-Smit concludes with a reflection on the future of international relations in an era of profound global change. --